Recognition In Asean Free Trade - Nisa, Lailatul; Sebayang, Septian Mixrova; Siwi, Adiratna Sekar (Al Makki Publisher, 2023)
Palliative care is aimed at the patient's recovery process in accepting the illness he is suffering from, and palliative care is to reduce the suffering experienced by the patient. This study aimed to determine nurses' level of knowledge and caring behavior in palliative care. This type of research is quantitative with a cross-sectional approach. The sampling technique uses convenience sampling. The sample of this study is nurses finding 63. The measuring instruments used in this study are Palliative Care Quiz For Nursing (PCQN) and Caring Behaviors Inventory (CBI). Statistical analysis using Spearman rank correlation test. The study results obtained a 2-tailed Sig value of 0.000 (p-value> 0.005), thus indicating a relationship between knowledge and nurse behavior. This research is expected to illustrate Nurse's nursing behavior in providing care to palliative patients.